2019
DOI: 10.1002/cmdc.201900575
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Biased Mu‐Opioid Receptor Agonists for the Treatment of Pain

Abstract: G protein‐biased mu‐opioid receptor (MOR) agonists have been developed as promising new potent analgesic drugs with fewer adverse side effects than standard MOR agonists. PZM21 represents a unique chemotype unrelated to known opioids, which makes it a desirable lead for modification to find analgesics with new chemical entities. In the present study, we synthesized and tested novel PZM21 derivatives as potent biased MOR agonists by introducing a benzodioxolane group to replace the hydroxybenzene of PZM21. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…After intrathecal administration, PZM21 mimicked morphine, producing naltrexone sensitive antiallodynic effects associated with long-lasting scratching [ 58 ]. The chemical template of PZM21 has been used for structure activity relationship studies that led to the identification of novel G-protein-biased mu-receptor agonists [ 59 , 60 ].…”
Section: Pharmacological Studies—are Mu-receptor Agonists Biased Tmentioning
confidence: 99%
“…After intrathecal administration, PZM21 mimicked morphine, producing naltrexone sensitive antiallodynic effects associated with long-lasting scratching [ 58 ]. The chemical template of PZM21 has been used for structure activity relationship studies that led to the identification of novel G-protein-biased mu-receptor agonists [ 59 , 60 ].…”
Section: Pharmacological Studies—are Mu-receptor Agonists Biased Tmentioning
confidence: 99%
“…1 H NMR (800 MHz, CDCl 3 ): δ 11.55 (s, 1H), 10.23 (s, 1H), 7.40 (t, J = 7.7 Hz, 1H), 7.35−7.30 (m, 1H), 7.17 (t, J = 7.5 Hz, 1H), 7.11 (t, J = 9.1 Hz, 1H), 6.77 (s, 1H), 6.05 (s, 1H), 3.81 (s, 2H), 2.44 (q, J = 7.5 Hz, 2H), 2.26 (s, 3H), 1.24 (t, J = 7.4 Hz, 3H). 13 (36). Prepared using general procedure A using 2-(m-tolyl)acetic acid (0.045 g, 0.30 mmol, 1.3 equiv), BTFFH (0.11 g, 0.34 mmol, 1.5 equiv), DCM (0.5 mL), DIPEA (180 μL, 1.0 mmol, 4.3 equiv), and 5 (0.050 g, 0.23 mmol, 1 equiv).…”
Section: Hz 3h) Apci-ms M/z: 2201 [M + H] +mentioning
confidence: 99%
“…35 One potential approach under investigation to limit these side effects is the development of biased MOR agonists that favor signaling through the G protein pathway and reduce the βarrestin pathway signal. 36 Alternatively, our group and others have shown that it is possible to target the activity of the downstream AC directly, bypassing the MOR entirely. 37−39 This strategy would allow for effective inhibition of chronic pain through AC inhibition, while avoiding negative side effects induced by clinically used MOR agonists, thus increasing the therapeutic index.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[142,143] However, given that the majority of clinically efficacious opioid analgesics require interaction with the MOR, there is still substantial interest in developing μ-agonists with reduced side effects. [144] From a physiological viewpoint, pain is often associated with acidosis of the injured tissue. [145] Classical SAR data has shown that for efficient interaction with the MOR, compounds must preferentially feature a protonatable tertiary amine.…”
Section: Case Study: Modulation Of Pk Amentioning
confidence: 99%